Cucurbitacin E Induces G2/M Phase Arrest through STAT3/p53/p21 Signaling and Provokes Apoptosis via Fas/CD95 and Mitochondria-Dependent Pathways in Human Bladder Cancer T24 Cells. (9th January 2012) - Huang, Wen-Wen; Yang, Jai-Sing; Lin, Meng-Wei; Chen, Po-Yuan; Chiou, Shang-Ming; Chueh, Fu-Shin; Lan, Yu-Hsuan; Pai, Shu-Jen; Tsuzuki, Minoru; Ho, Wai-Jane; Chung, Jing-Gung
Abstract : Cucurbitacin E, a tetracyclic triterpenes compound extracted from cucurbitaceous plants, has been shown to exhibit anticancer and anti-inflammatory activities. The purpose of this study was to elucidate whether cucurbitacin E promotes cell cycle arrest and induces apoptosis in T24 cells and further to explore the underlying molecular mechanisms. The effects of cucurbitacin E on T24 cell's growth and accompanied morphological changes were examined by MTT assay and a phase-contrast microscope. DNA content, mitochondrial membrane potential (Δ Ψ m ) and annexin V/PI staining were determined by flow cytometry. The protein levels were measured by Western blotting. Our results demonstrated that cucurbitacin E-induced G2 /M arrest was associated with a marked increase in the levels of p53, p21 and a decrease in phospho-signal transducer and activator of transcription 3 (STAT3), cyclin-dependent kinase 1 (CDK1) and cyclin B. Cucurbitacin E-triggered apoptosis was accompanied with up-regulation of Fas/CD95, truncated BID (t-BID) and a loss of Δ Ψ m, resulting in the releases of cytochrome c, apoptotic protease activating factor 1 (Apaf-1) and apoptosis-inducing factor (AIF), and sequential activation of caspase-8, caspase-9, and caspase-3. Our findings provided the first evidence that STAT3/p53/p21 signaling, Fas/CD95 and mitochondria-dependent pathways play critical roles in cucurbitacin E-induced G2 /M phase arrest and apoptosis of T24 cells.